Effective location of thyristor controlled series capacitor by sensitivity based method for congestion management - Abu Bakar, Noorsakinah (2015)
Increasing dependency of electrical energy has led to rapid growth of power system which results to few uncertainties. Instability problem in power systems have become one of the most important concerns in the power industry which lead to blackouts. Power disruption and individual power outage one of the major problem affect the economy of the country. If the exchanges were not controlled, some lines located on particular paths may become overloaded or congested. Plus, uncontrollable reactive power losses results to instability to maintain the voltage at all the buses around the nominal value lead to voltage collapse. It is important to have high efficiency, maximum reliability, and security in design and operation of power system. Recent development of power electronics introduces the use of Flexible AC Transmission System (FACTS) controllers in power systems. FACTS controllers are capable of controlling the network condition in a very fast manner and this feature of FACTS can be exploited to improve the stability of a power system. The aim of this project is to study the effect of Thyristor Controlled Series Capacitor (TCSC) to mitigate contingencies in transmission line by locating TCSC at the most sensitive line thru reactive power loss sensitivity indices approach. This project also focus on total reactive power loss reduction and transmission line loadability on tested small network (5 bus) and large network (modified IEEE 14 bus) system. Apart from that, the effect of degree of compensation of TCSC as well been studied. These studies and investigation was carried out using MATLAB/MATPOWER 5.0 and Power World Simulator GSO 18. This project concludes that the proposed approach is efficient for solving line contingencies, power losses reduction and line loadability in which meet the objectives of this research.